The Effects of Age and Pubertal Changes on Cognitive Appraisal Biases in Youth with Social Anxiety Disorder - Zhou, Anna M. (Tufts Archival Research Center, 2015)
Cognitive-behavioral models of Social Anxiety Disorder (SAD) have posited cognitive appraisal biases as an underlying causal factor in the development and maintenance of the disorder; studies have suggested that age and pubertal status moderate the presence of cognitive biases in children with SAD. The present study aims to examine age and pubertal changes in cognitive appraisal biases on a social-evaluative task in youth with SAD. In this single-session exposure study, youth with SAD and non-anxious controls (aged 8 to 14) were compared on various self-report measures of anxiety. They also rated their perception of performance after giving a speech before and after receiving positive feedback. Additionally, an observational coding system was developed to assess valence and content of children’s utterances during a cognitive restructuring task. Results showed that age and pubertal status were significant negative predictors of self-ratings on speech performance both pre-feedback and post-feedback. However, age and pubertal stage were not significant predictors of negative performance cognitions, but they were significant positive predictors of the total number of cognitions related to performance. The current findings suggest that there are developmental effects on cognitive appraisal biases in youth with SAD, such that older children with SAD have more negative biases when evaluating their performance on a social evaluative task post-feedback. Additionally, cognitive components of treatment may want to focus more on rationalizing and generalizing exposures with younger children instead of restructuring and modifying cognitive biases given that younger children with SAD did not exhibit the same cognitive appraisal biases as older children with SAD.